Frontoparietal control of spatial attention and motor intention in human EEG. - Praamstra, P; Boutsen, L; Humphreys, G (2005)
Relations between spatial attention and motor intention were investigated by means of an EEG potential elicited by shifting attention to a location in space as well as by the selection of a hand for responding. High-density recordings traced this potential to a common frontoparietal network activated by attentional orienting and by response selection. Within this network, parietal and frontal cortex were activated sequentially, followed by an anterior-to-posterior migration of activity culminating in the lateral occipital cortex. Based on temporal and polarity information provided by EEG, we hypothesize that the frontoparietal activation, evoked by directional information, updates a task-defined preparatory state by deselecting or inhibiting the behavioral option competing with the cued response side or the cued direction of attention. These results from human EEG demonstrate a direct EEG manifestation of the frontoparietal attention network previously identified in functional imaging. EEG reveals the time-course of activation within this network and elucidates the generation and function of associated directing-attention EEG potentials. The results emphasize transient activation and a decision-related function of the frontoparietal attention network, contrasting with the sustained preparatory activation that is commonly inferred from neuroimaging.